ESG Stewardship Regulations of Some Countries and Suggestions for Viet Nam - Quynh Anh, Nguyen Thi (VNU Journal of Science: Legal Studies; Vol 42 No 1, 2026)
Environmental, Social, and Governance (ESG) Stewardship has become an emerging trend in contemporary corporate governance. Accordingly, integrating ESG standards into business operations has become an inevitable and urgent requirement. The article introduces the global ESG stewardship ecosystem, examines the legal frameworks in several countries that support ESG stewardship, and proposes several recommendations for ESG management policies in Vietnam.